"Dancing Naked": Gender, Trauma and Politics in the Mystical Poetry of Lal Ded. Issue 1 (3rd April 2022) - Bazaz, Abir
Abstract: Lal Ded, the fourteenth century Kashmiri female mystic, is revered as a spiritual exemplar by both the Hindus and the Muslims of Kashmir. She walked away from a difficult marriage at the young age of twenty-six to pursue the Śaiva path to spiritual liberation. Lal Ded records her long and arduous spiritual journey in a Kashmiri poetic form, vākh (a short poem of four lines with four stresses in each line), which is also one of the earliest genres of Kashmiri poetry. Even though most scholarship on Lal Ded's vākhs does invoke her difficult life as a Kashmiri woman in a turbulent political milieu, it rarely poses the question of gender and politics in relation to her mystical poetry. My paper offers a close reading of selected vākhs to argue that the figures of loss (rāvan-tyol, loss-blister), shame (mandchhi hạ̄nkal, iron fetters of shame) and joy (nangaē natsun, dancing naked) in Lal Ded's mystical poetry can be read not merely as stages on the path of a Śaiva liberation but also as a distinctive proto-feminist perspective on political self-transformation.